A Mini Review on the Microvia Filling Technology Based on Printed Metal Nano/Microparticles - Yang, Guannan; Luo, Shaogen; Li, Zhen; Zhang, Yu; Cui, Chengqiang (Frontiers in Materials, 2022)
Microvia filling is a core interconnection technique in electronic manufacturing. Electroplating is the primary method used in industry for filling microvias, but also has the drawbacks of cumbersome procedures and toxic by-products. New microvia filling technology through printing of metal based conductive fillers was then developed, with the advantages of simpler process, higher efficiency, better compatibility, and eco-friendliness. Here we reviewed the up-to-date research findings on the microvia filling technology based on printed metal nano-microparticles from the perspectives of material development and filling performance. Some key questions about this technology are also discussed. We hope the outlook presented by this review could help the further studies on this topic. The review also identifies some key remaining issues to be resolved.